(untitled) (Journal of Informatics and Mathematical Sciences, 2014)
Starting with convergence and absolute convergence of double Laplace integral uniform convergence of double Laplace transform is presented. Finally, a Volterra Integro-Partial Differential Equation is solved by using double Laplace transform.